5-5d=3d-3

Simple and best practice solution for 5-5d=3d-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-5d=3d-3 equation:


Simplifying
5 + -5d = 3d + -3

Reorder the terms:
5 + -5d = -3 + 3d

Solving
5 + -5d = -3 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
5 + -5d + -3d = -3 + 3d + -3d

Combine like terms: -5d + -3d = -8d
5 + -8d = -3 + 3d + -3d

Combine like terms: 3d + -3d = 0
5 + -8d = -3 + 0
5 + -8d = -3

Add '-5' to each side of the equation.
5 + -5 + -8d = -3 + -5

Combine like terms: 5 + -5 = 0
0 + -8d = -3 + -5
-8d = -3 + -5

Combine like terms: -3 + -5 = -8
-8d = -8

Divide each side by '-8'.
d = 1

Simplifying
d = 1

See similar equations:

| -194=-5x+4(-5x+14) | | 5(2n+5)=8(7n+7)7 | | 0=4y+6 | | 5x/6=14 | | 9+4n=69-6n | | -34+6x=38 | | 3x+3x+x+x=1000 | | -7x+2(4x+18)=42 | | 4=2x+10/2 | | 5(3n+2)=7(8n+1)+6 | | 13=8x-51 | | 27/3*5+4-2 | | 0.8x-4.5=0.3 | | 27/3x5+4-2 | | -83=3x+4(-3x+5) | | -83=3x-3(6x+5) | | 18=9y-9 | | x^2+4=26 | | x=4y+6 | | 164=-6x-4(-5x-6) | | 6x-24+6=4x+2x-12 | | 2x+50=500 | | 0.04(y-8)+0.02y=0.10y-0.3 | | -5c-11=29 | | 170=24-w | | 0.04(y-8)+0.02=0.10y-0.3 | | 2m-9=3 | | 310s-278=722-199s | | 4(3x+x)+7-5=8+(-5)(5x-6x)+23 | | 5y/12-8=9-3y/4 | | -195=3x-3(6x+5) | | 29=4x+3(-3x-2) |

Equations solver categories